Visions of the vanquished. Heterogeneous and divergent memories - García-Bedoya Maguiña, Carlos (2017)
This article studies two texts that represent the divergent perspectives of different factions of the Inca elite towards the Spanish conquest: the Relacion de los Quipucamayos, compiled initially in 1542, and Tito Cusi's Instruccion, written in 1570. The former expresses the point of view of the sector that decided to adapt to the new order established by the victorious Spaniards; it exalts the contributions of Inca Paullu and the merits of his descendants. The latter expresses the perspective of the sector that favored the resistance against Spanish conquest, but also negotiation, and exalts Manco Inca and his successors, who ruled until 1572 the so-called Neo Inca state in Vilcabamba. Text analysis will focus on the discursive construction of the divergent memories of those "vanquished" in the process of imposition of colonial domination.